Assessment of the Stability and Response of a Catamaran-Hull Ferry to Operational and Environmental Conditions - Santoso, Budhi; Romadhoni, Romadhoni; Ariany, Zulfaidah; Ridwan, Muhammad (Department of Naval Architecture - Diponegoro University, 2024)
Ship stability is a critical factor in the operation of a catamaran, especially when facing various sea conditions. The catamaran H-192, recently acquired by PT XY, is used as a case study in this research to assess its stability and response to operational and environmental conditions. Stability criteria based on Annex 7 of the High-Speed Craft (HSC) Code are used as the evaluation standard. This research aims to evaluate the stability and response of the catamaran H-192 under various operational and environmental conditions. The primary focus is to ensure that the vessel meets and exceeds the stability criteria set by Annex 7 and to understand how the vessel behaves in real-world situations. The methods used in this research include stability calculations based on Annex 7 and model design using Maxsurf software. The calculations involve the analysis of the righting lever (GZ), metacentric height (GM), and other stability criteria. Operational data and load distribution are analyzed to determine the draft, trim, and stability of the vessel under various loading conditions. The results show that the catamaran H-192 not only meets but also exceeds the stability criteria set by Annex 7. The high values of righting lever (GZ) and metacentric height (GM) at various angles of heel indicate excellent transverse and longitudinal stability. The evaluation of intact stability criteria shows that all parameters achieve